Effects of planning regulations on housing and land markets: A system dynamics modeling approach. (July 2022) - Jalali, Danon; MacDonald, Heather; Fini, Alireza Ahmadian Fard; Shi, Song
Abstract: The effect of planning regulations on housing and land markets has been a long-lasting concern. The inherent complexities of incorporating regulations into models, including the heterogeneity of regulations and their temporal effect, have resulted in different approaches, and consensus has been elusive. Few studies have addressed the effect of regulations in a dynamic framework of the housing and land markets. In these studies, different regulations or the indices capturing their restrictiveness are assumed to have a linear additive effect along with the other factors. The results have been contradictory. This paper aims to model the dynamic effect of regulations by incorporating them in a causal rather than correlational form of relationships. To this end, we adopted the system dynamics approach to model the individual effect of three important types of regulation widely used in urban planning systems: maximum building density, minimum lot size, and urban growth boundary. We use the concept of optimum building density to integrate the housing market and the land market through the construction sector, providing clearer causal links among the related markets. To our knowledge this is the first use of this concept in a dynamic model. We ran the simulations (using hypothetical parameters) to analyze the effect of each regulation on housing and land price changes. The simulation results show that by imposing more restrictive UGBs, housing and land prices increase. A more restrictive MBD first results in a decrease in the land price and, then, due to its effect on the whole housing market, increases both housing and land prices. A more restrictive MLS has a short-term impact on land and housing prices, but it does not change long-run price levels. The common feature of the market under more restrictive forms of all three regulations is lower volatility. Highlights: The systems dynamic model addresses complexities related to time, heterogeneity of regulations, and endogeneity. After a demand shock, increasing Maximum Building Density causes land prices to decline and housing prices to increase Introducing an Urban Growth Boundary increased both housing and land prices. Increasing the minimum lot size resulted in very small increases in prices in the short term only. More restrictive versions of regulations reduced market fluctuations.